Stage lighting and site specific theater: notes about lighting in the Biblical Trilogy of Teatro da Vertigem (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
The article seeks to weave relations between the work of scenic lighting and the site specific nature of some theatrical works. Starting from the principle that the theatrical work is constituted from the interaction of its parts, it seeks to understand the lighting as an articulating element of spatiality. Based on a conceptual framework on the term site specific, the article presents three performances as examples of these relationships: O Paraíso Perdido, O Livro de Jó e Apocalipse 1,11, all three creations by the Teatro da Vertigem with lighting design by Guilherme Bonfanti.
Keywords: site specific; stage lighting; Teatro da vertigem; Guilherme Bonfanti